Superstars need Social Benefits: An Experiment on Network Formation - Boris van Leeuwen; Theo Offerman; Arthur Schram (Tinbergen Institute, 2013)
We investigate contributions to the provision of public goods on a network when efficient provision requires the formation of a star network. We provide a theoretical analysis and study behavior in a controlled laboratory experiment. In a 2x2 design, we examine the effects of group size and the presence of (social) benefits for incoming links. We find that social benefits are highly important. They facilitate convergence to equilibrium networks and enhance the stability and efficiency of the outcome. Moreover, in large groups social benefits encourage the formation of superstars: star networks in which the core contributes more than expected in the stage-game equilibrium. We show that this result is predicted by a repeated game equilibrium.
Keywords: C91; D85; H41; 330; Network formation; networked public goods; peer production; social benefits; open source software